Sistem Pendukung Keputusan Untuk Penentuan Siswa Teladan Menggunakan Metode Weighted Product - Arfandi, Rivaldi Maulana; Purbaningtyas, Rani (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
Each school will determine the role model at the end of each semester to measure the competency test of each student. However, in determining exemplary students in schools, it always creates inspiration among the teacher councils because each teacher council has each to see exemplary students in schools. The Support System (SPK) or Decision Support System (DSS) is an information system intended to assist schools in solving student decision problems. One of the methods used in the decision support system is the Weighted product. The criteria used are academic and non-academic. Furthermore, the criteria will be divided into sub-criteria according to the provisions of the school. With this model student application, it really helps the teacher council to solve the problems that students expect at school.